Factores psicológicos sociales y culturales asociados al embarazo adolescente (2021)
The present study has as a research question: What are the factors psychological, social and cultural associated with adolescent pregnancy in the community of Villa Fátima neighborhood of the Special Tourist and Cultural District of Riohacha? Based on this problematic situation the general objective of the study is stated: Analyze the factors psychological, social and cultural associated with adolescent pregnancy.